KEMAMPUAN ANALOGI MATEMATIS MAHASISWA PADA MATA KULIAH KALKULUS DIFFERENSIAL - Gunawan Gunawan; Fitrianto Eko Subekti (KALAMATIKA Jurnal Pendidikan Matematika, 2018)
This research aims to describe the students capability in mathematics analogy at the subject of differential calculus. The technique in taking the sample uses “purposive sampling technique”. It takes three students from each category, they are low, medium, and high. From the low category must of students haven’t understood get the concept used the solve the problem, not only the problem of the source but also the problem of target. For the medium category most of the students have understood the concept, and the similiar concept used, but they dont’t have the cabability to apply in solving the problem. Whereas for the high category most of the students have understood the similiar concept, the concept that is used and have capability to apply it to solve the problem of the source and target.